2014
DOI: 10.1093/jxb/eru018
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of phytochelatins in roots of rice to long-term exposure: evidence of individual role on arsenic accumulation and translocation

Abstract: SummarySix varieties of rice were exposed to low and high levels of arsenic in the same soil. Their individual responses of expressing phytochelatins have been correlated to inorganic arsenic uptake, transport, and accumulation in the rice grain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(83 citation statements)
references
References 52 publications
(85 reference statements)
3
75
1
4
Order By: Relevance
“…Samples were treated according to Batista et al (2014). The determination of Al, Si, P, K, Ca, Mg, B, Mn, Fe, Cu, Zn and Ni was carried out using an inductively coupled plasma mass spectrometer (ICP-MS, Agilent 7900, Santa Clara, USA).…”
Section: Etermining Photosynthetic Pig Mentsmentioning
confidence: 99%
“…Samples were treated according to Batista et al (2014). The determination of Al, Si, P, K, Ca, Mg, B, Mn, Fe, Cu, Zn and Ni was carried out using an inductively coupled plasma mass spectrometer (ICP-MS, Agilent 7900, Santa Clara, USA).…”
Section: Etermining Photosynthetic Pig Mentsmentioning
confidence: 99%
“…As shown in Table 2, wheat root As was found to be positively correlated with root Cd (Table 2). One pos- sible reason for this is the different levels of phytochelatin (PC) synthesis in different wheat cultivars under As and Cd exposure [49,50]. Cultivars with a higher PC production may have higher As and Cd tolerance, as well as a higher capacity for As and Cd accumulation [50][51][52].…”
Section: Grain Asmentioning
confidence: 99%
“…One pos- sible reason for this is the different levels of phytochelatin (PC) synthesis in different wheat cultivars under As and Cd exposure [49,50]. Cultivars with a higher PC production may have higher As and Cd tolerance, as well as a higher capacity for As and Cd accumulation [50][51][52]. In addition, some metal transporters such as NRAMP1 (Natural Resistance-Associated Macrophage Protein) maybe contribute to the enhancement of both As and Cd accumulation in plants.…”
Section: Grain Asmentioning
confidence: 99%
“…7 (Grill et al, 2002;Klapheck 1988). Leguminosae (Klapheck et al, 1995), graminae (Batista et al, 2014;Oven et al, 2002), maize (Chassaigne et al, 2001), horseradish (Kubota et al, 2000) and some species of fungi (Collin-Hansen et al, 2007) have been found to produce hGSH and hPC in addition to GSH/PC (Mounicou et al, 2001), which can give an even greater redox buffering capacity than that observed for C. vulgaris.…”
Section: Arsenic (Iii) Effects In C Vulgarismentioning
confidence: 99%